Treatment of Ongoing Hemorrhage The Art and Craft of Stopping Severe Bleeding (Springer International Publishing, 2018)
This volume provides a concise yet comprehensive review of techniques for stopping ongoing hemorrhage in all areas of the body. The text discusses open surgical techniques and minimally invasive (percutaneous, endoscopic, radiologic, laparoscopic) approaches, as well as techniques appropriate to pre-hospital settings, such as "on the scene", ambulance, and the battlefield. The techniques and tips are delivered in a detailed, yet simple and straight-forward manner so that readers are more readily able to replicate these concepts in the face of ongoing, life-threatening hemorrhage. Written by experts in the field, Treatment of Ongoing Hemorrhage: A Practical Guide is a valuable resource for surgeons, trainees, and any physician who works within the emergency department or upon critically ill patients.